Pengaruh Media Visual Berbasis Canva Terhadap Hasil Belajar Mata Pelajaran IPAS pada Siswa Kelas III SDN Dr. Sutomo I Surabaya - Azizah, Nur; Suprihatien, Suprihatien; Jarmani, Jarmani (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze whether canva-based visual media has an influence on student learning outcomes. The sample of this study consisted of two groups, namely the control class and the experimental class. The analysis method used in this study is the experimental method, quantitative analysis. By conducting expert validity tests, pretests and t-tests using SPSS23. The results of the study indicate that canva-based visual media has an influence on student learning outcomes at SDN Dr. Sutomo I Surabaya.